Eduardo milan’s constantly reaching something else: symbol, allegory and fragment - López Carballo, Pablo (Revista Chilena de Literatura, 2018)
Eduardo Milán’s oeuvre is characterized by constant recourse to symbolic and allegorical strategies –as charged with a specifically metonymical function– to the detriment of other traditional rhetorical devices, such as those related to metaphor. These strategies, which the author considers as especially relevant for their scope and creative possibilities, clearly show his authorial stance towards language. Therefore, it is the instability of language, which does not allow the univocal determination of meanings and referents, which can be devised as a crucial aspect in the analysis of Milán’s poetry. Consequently, this paper focuses on an early stage of his poetry (1990-1994), in which the author uses the fragment as the basic unit for his creative processes.